2017
DOI: 10.3390/rs9060511
|View full text |Cite
|
Sign up to set email alerts
|

Independent System Calibration of Sentinel-1B

Abstract: Sentinel-1B is the second of two C-Band Synthetic Aperture Radar (SAR) satellites of the Sentinel-1 mission, launched in April 2016-two years after the launch of the first satellite, Sentinel-1A. In addition to the commissioning of Sentinel-1B executed by the European Space Agency (ESA), an independent system calibration was performed by the German Aerospace Center (DLR) on behalf of ESA. Based on an efficient calibration strategy and the different calibration procedures already developed and applied for Senti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 13 publications
4
60
0
Order By: Relevance
“…In addition, the soil contribution was simulated using the IEM modified by Baghdadi et al [15,17]. The results showed that the parameterized WCM simulates the backscattering coefficients in the VV and VH polarizations with an accuracy (Root Mean Square Error "RMSE") of approximately 1.4 dB (R 2 approximately 0.60), which is close to the S1 measurement accuracy [51,52].…”
Section: Radar Backscattering Modelmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, the soil contribution was simulated using the IEM modified by Baghdadi et al [15,17]. The results showed that the parameterized WCM simulates the backscattering coefficients in the VV and VH polarizations with an accuracy (Root Mean Square Error "RMSE") of approximately 1.4 dB (R 2 approximately 0.60), which is close to the S1 measurement accuracy [51,52].…”
Section: Radar Backscattering Modelmentioning
confidence: 88%
“…To make the synthetic database of backscattering coefficients more realistic (i.e., similar to real SAR data), the error corresponding to Sentinel-1 radiometric accuracy was added to the simulated backscattering coefficients. This error is approximately 0.70 dB (3σ) for the VV polarization and 1.0 dB (3σ) for the VH polarization [52]. Thus, we considered two absolute zero-mean Gaussian random additive noises with a standard deviation of ±0.7 and ±1.0 dB to be added to the simulated backscattering coefficients in the VV and VH, respectively.…”
Section: Synthetic Databasementioning
confidence: 99%
“…The correlation coefficient R2 is equal to 0.55 for VV and 0.63 for VH with RMSE (Root Mean Square Error) on the predicted backscattering coefficients of 1.55 dB in VV and 1.30 dB in VH. The RMSE obtained on the WCM predictions close to 1.5 dB are slightly higher than the Sentinel-1 precision [32,33]. Indeed, the radiometric accuracy for all measurement modes of Sentinel-1 is within 1 dB (3σ) and its sensitivity expressed by the noise equivalent sigma naught is −22 dB or higher [32].…”
Section: Water Cloud Model Validationmentioning
confidence: 93%
“…In order to make the IEM simulations more realistic, Sentinel-1 radiometric error was added to simulated backscattering coefficients. In Schwerdt et al [20], this error is about 0.70 dB (3σ) for VV polarization. Accordingly, zero-mean Gaussian random noise with a standard deviation of ±0.70 dB was added to simulated backscattering coefficients in VV polarization.…”
Section: Synthetic Datasetmentioning
confidence: 99%
“…The standard acquisition mode of Sentinel-1 corresponds to acquisitions in both VV and VH polarizations. Since the VH polarization produces low signal levels over bare soils and is strongly affected by noise (radiometric accuracy is about 1.0 dB (3σ) for VH [20], it is less commonly used for the analysis of surface parameters. Accordingly, only VV was used.…”
mentioning
confidence: 99%